Hepatopancreatobiliary Fellowship Graduates: Where Do They Stand today?. Issue 6 (June 2022) - Jackson, Terence; Lim, Joseph S.; Cho, Edward; Osman, Houssam; Nagatomo, Kei; Jeyarajah, Dhiresh Rohan
Background: The Americas Hepato-Pancreato-Biliary Association (AHPBA) Education and Training Committee standardized a Hepatopancreatobiliary (HPB) Surgery Fellowship certification process in 2010. Several classes of fellows have since graduated from HPB, combined Society of Surgical Oncology/AHPBA, and combined American Society of Transplant Surgeons/AHPBA fellowships, but there is little information on their career outcomes. We seek to offer long-term data on the careers of HPB fellowship graduates. Methods: A 26-question anonymous survey was distributed among graduates of accredited programs for the last 10 years. We generated descriptive statistics from the responses. Results: The respondents were evenly distributed in terms of graduation years between 2010 and 2019. Fifty-eight percent of fellows had completed a prior fellowship, 82% received 1 to 3 job offers during the fellowship, and 75% of respondents were still at their first job. The majority of graduates (>60%) were able to secure a job with a >50% HPB practice and >40 HPB cases per year within 3 years of graduation. Overall, >90% candidates rated their satisfaction with fellowship training greater than 8 out of 10. Discussion: This survey helps shed light on the early formative years in the practices of HPB fellowship graduates. These data show that HPB fellowship training is essential and effective in providing job security and helps fellowship graduates develop a gratifying practice.